Microsoft Windows 2000 API superbible - Simon, Richard J. (Sams, 2000)
Following in the tradition of the Win 95 and Win32 NT SuperBibles, this book is a comprehensive reference for all of the APIs needed by the Windows programmer. It is arranged topically with related functions presented in the same chapter. Using relevant examples that are complete and appropriate to the task at hand, the user will be able to see clearly the most effective usage for each function. The user-friendly organization of the book will save programmers valuable time, and negate the need to sift through vendor supplied documentation with is spotty and disorganized.